2016
DOI: 10.15547/bjvm.930
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy rate in dry and lactating goats after estrus synchronisation with artificial insemination and natural breeding (a field study)

Abstract: SummaryYotov, S., A. Atanasov, M. Karadaev, L. Dimova & D. Velislavova, 2016. Pregnancy rate in dry and lactating goats after estrus synchronisation with artificial insemination and natural breeding (a field study). Bulg. J. Vet. Med., 19, No 3,[218][219][220][221][222][223] The objective of this study was to determine the pregnancy rate in dry and lactating goats after estrus synchronisation with artificial insemination and natural breeding of unconceived animals. The investigation was conducted with 75 dry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…While, Yotov. [35] demonstrated that accuracy of pregnancy detection was high (87%) at week 4 post-breeding, and it increased to 98% at day 35 post-mating using a 5 MHz transabdominal probe in Satara Zagora sheep breed. The ultrasonography examination method on day 50 can be considered a gold standard for pregnancy diagnosis, given the high diagnostic criteria and reliability recorded (100%) [36].…”
Section: Resultsmentioning
confidence: 94%
“…While, Yotov. [35] demonstrated that accuracy of pregnancy detection was high (87%) at week 4 post-breeding, and it increased to 98% at day 35 post-mating using a 5 MHz transabdominal probe in Satara Zagora sheep breed. The ultrasonography examination method on day 50 can be considered a gold standard for pregnancy diagnosis, given the high diagnostic criteria and reliability recorded (100%) [36].…”
Section: Resultsmentioning
confidence: 94%
“…In many cases, the use of the standard technique results in deposition of the semen in the cervix if all the cervical rings cannot be passed. Under controlled conditions, pregnancy rates following the use of the standard technique are low, typically in the range of 20-30% [41][42][43][44].…”
Section: Standard Ai Methods (Tube Speculum)mentioning
confidence: 99%
“…The urinary catheter is then repositioned into the opposite uterine horn, and the second half of the semen sample is deposited deep into that horn to complete the insemination. With trained technicians, the entire procedure takes about 5-10 min [41] and does not involve any surgical entry or anesthesia of the doe. Furthermore, pregnancy rates following deep cornual insemination were greater than those for laparoscopic insemination in their study.…”
Section: Goat Sciencementioning
confidence: 99%